Oral manifestations in diabetes mellitus- a review - Subham Kumari; N Gnanasundaram (Wolters Kluwer Medknow Publications, 2021)
This article deals with the characteristic of clinical findings of diabetes mellitus (DM) in the mouth and teeth. Identification of these findings in the examination of the mouth will help to diagnose DM. Symptoms such as dryness of the mouth (xerostomia), burning sensation, painful gingival swelling, and mobility of teeth due to uncontrolled DM are explained. Signs such as gingivitis, periodontitis, multiple periodontal abscesses, and fungal lesions such as Candidiasis are explained. Oral symptoms and signs may enable medical and dental specialists to diagnose diabetes. Proper diagnosis will ensure proper treatment. "Diabetes is a good disease with bad companions" quoted Dr. Sam G. P. Mosses, a renowned diabetologist in India. It is true. Diabetes is a biochemical disorder where there is a failure of peripheral utilization of sugar in cells due to insulin deficiency or defectiveness causing accumulation of excess sugar in the tissues, thus leading to hyperglycemia, glycosuria, polyuria, polyphagia, and polydipsia. It is difficult to find out when exactly the disease develops with a hyperglycemic state and how to identify the disease in the early stages. Diabetes is a reversible disease and can be controlled by restoring sugar metabolism by correcting insulin deficiency or defectiveness. Thus, the complications are considered as the bad companions of this disease. DM is a disease with systemic involvement affecting various structures and organs. The mouth is also affected by DM. If a medical or dental specialist is fully familiarized with Oral changes in DM, they can diagnose the undiagnosed diabetes through the examination of the mouth. Further confirmation of diagnosis can be made by a biochemical study of blood and urine. This article elaborates and explains the various mouth changes in diabetics for diagnosis and management.